Corrosion Rate of Carbon Steel A106 Gr B in Amine-CO2 Contained Solutions - Yuli Panca Asmara; Tedi Kurniawan; Kushendarsyah Saptaji (Faculty of Engineering and Technology, Sampoerna University, 2021)
Carbon dioxide (CO2) is one of the corrosive element which exists in oil and gas industries. To prevent CO2 corrosion on carbon steel pipelines, amine-base solvent and caustic solutions are commonly applied. Accordingly, effectiveness of amine base solvent and caustic solutions to reduce risk of corrosion becomes key parameters in determining service lifetime of pipelines made of carbon steel. In this research, the corrosion rate of carbon steel A106 Gr B in amine solutions combined with saturated CO2 gas and caustic solution was studied. The experiments were carried out in static conditions and the Linear Polarization Resistance (LPR) technique was used to measure the corrosion rate (as per ASTM G 5-94). It was found that the corrosion rate in the amine-based solution had shown remarkable results. Somehow, the corrosion rate in an amine-based solvent containing saturated CO2 gas has increased to 200%. The temperature increment to 50°C from room temperature has also increased the corrosion rate. Meanwhile, the caustic addition in amine solution has reduced the corrosion rate of carbon steel.